Knowledge and practices about oral health among teachers in two schools: Quito and San Cristobal island (Galapagos), Ecuador - Armas Vega, Ana (2020)
Objective: To analyze the knowledge, attitudes and practices that oral health teachers have in primary schools in Quito and San Cristobal Island (Galapagos), Ecuador. Methods: The research began with the validation of the self-surveyed survey on knowledge, attitudes and practices on oral health in teachers (CAPS teachers). Subsequently, this instrument delivered to 61 teachers from the two schools selected for the study. The descriptive statistics of these data were obtained, including the absolute and relative frequencies of the responses obtained. Results: The average score obtained in the total evaluation of the 61 teachers was 11.97 ± 2.37 points. When the data were analyzed by schools, the Quito school obtained an average of 12.06 ± 2.29, while the Galapagos school obtained an average of 11.29 ± 3.04 points. Conclusions: The knowledge in oral health of the teachers of the two educational centers was acceptable; there was no difference in the score of the total evaluation due to their origin.